Changing the Academic Integrity Climate on Campus Using a Technology-Based Intervention. Issue 2 (17th February 2017) - Cronan, Timothy Paul; McHaney, Roger; Douglas, David E.; Mullins, Jeffrey K.
Abstract : This article focuses on the use of a technology-based intervention to change academic integrity (AI) knowledge and attitudes. Using a sample of more than 5, 000 freshman students drawn from two major midwestern universities in the United States over a 3-year period, an online intervention was used to determine whether AI knowledge and attitudes could be changed. Based the results of this study, AI knowledge and attitudes can be improved using an online intervention. These results contribute to a better understanding of the AI climate on campus and suggest that technology-based interventions can be used to enhance knowledge and change attitudes toward AI on campus.